Inquiry-Based Learning Untuk Meningkatkan Hasil Belajar Keterampilan Dasar Pada Pelajaran Tindakan Keperawatan - Safitri, Diana (Perkumpulan Alumni dan Santri Mahyajatul Qurro', 2021)
In the Millennial era, learning should prioritize learning based on student-centered approaches based on self-direct learning, namely the Inquiry-based learning (IBL) model. This model is expected to enable students to apply self-direct learning. The purpose of this study was to determine the implementation of learning in Nursing Action Basic Skills Subjects for Patient Bed Preparation, to determine the application of the IBL model, and to determine the improvement of student learning outcomes in the 2021/2022 academic year. This research is classroom action research using cycles. The final result of this research is that the implementation of learning with the Inquiry-based learning model gives an excellent impression for students, with a percentage of 70% of the questionnaires, while the learning outcomes in the first cycle with 77% completeness and in the second cycle with 100% completeness. The percentage increase in learning outcomes from each cycle is 15.7% in the first cycle and 11.6% in the second cycle.